The Application of Flip-Debate as a New Approach to Dialogic Teaching Methodology - Mizan Binti Muhammed (22590488) (2025)
This conference contribution was presented by Mizan Binti Muhammed, Mohd Nazim Mat Nawi, Zainurin Abdul Rahman International Islamic University Malaysia, Malasya (International Conference on Debate and Dialogue. An Initiative of QatarDebate 2025). In the higher learning milieu, dialogic teaching is found to be an effective methodology which transcends the traditional one-way transmission of knowledge, yet research has shown that its application still faces many limitations and challenges. This paper introduces flip-debate, an innovative structured debate activity rooted in the Toulmin model of argumentation, as a new approach to dialogic teaching in the context of law foundation course. Flip-debate is adapted based on the existing competitive debate formats, with an insertion of curated prompts to stimulate inquiry and address the issue of lack of confidence among students who are unfamiliar with debates. Analysis of students’ feedback on its effectiveness in achieving the learning outcome that is ability to deliver argumentative speech was run using the T-Test and correlation measure. Results suggest that flip-debate fosters critical thinking, construction of arguments, and respectful disagreement, skills which align seamlessly with the demands of 21st century education. Other Information Conference information: The 2nd International Conference on Debate & Dialogue : An Initiative of QatarDebate (19 - 20 May 2025, Qatar National Conventions Center - QNCC, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://qatardebate.org/programs/academic-programs/2nd-icdd/